Model terapi gen menggunakan sel fibroblas rekombinan yang dibungkus mikrokapsul. Suatu Kajian In Vivo - M. Mansyur Romi, M. Mansyur Romi (Universitas Gadjah Mada, 1996)
Current approaches to human gene therapy focus on insertion of a desired gene into autologous cells such as fibroblasts. hepatocytes, bone marrow stem cells or lymphocytes. An alternate strategy to gene therapy through genetic modification of the patients own cells is to implant into different recipients the same engineered cell line under immunologically isolated conditions. This in vivo study shows that human growth hormone (hGH) as a novel reporter gene product from microencapsulated genetically modified mouse cells is detectable in the circulation of allogenic recipient mice. On day 3 of post implantation no hGH was detected, 3 ng/ml of hGH was detected on day 12 and increased during the next 9 days up to 10-fold. The high level of hGH was maintained during days 21 - 33 post implantation and went down afterward to the baseline on day 45. No hGH was detected in the control mouse implanted with the same amount of free recombinant cells.Key Words: Gene therapy - autologous cells - genetic modification - recombinant cells - lymphocytes